2021
DOI: 10.3390/molecules26082227
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Aromatic Molecules with 1,4-Diaza Groups for Flow Battery Applications

Abstract: The aqueous redox flow battery is a promising technology for large-scale low cost energy storage. The rich possibilities for the tailoring of organic molecules and the possibility to discover active materials of lower cost and decreased environmental impact continue to drive research and development of organic compounds suitable for redox flow battery applications. In this work, we focus on the characterization of aromatic molecules with 1,4-diaza groups for flow battery applications. We examine the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…Pristine pyrazine itself belongs to the first group in which it is reversibly reduced to protonated 1,4‐dihydropyrazine by accepting two electrons and three protons. Its reversibility was decreased by the substitution of electron ‐withdrawing or ‐donating groups, and the reversibility can change based on electrode type and supporting electrolyte used [ 50 , 51 ]. The CVs show that the reduction of FAV is included in the third category because the pyrazine ring in the FAV molecule was substituted with three different groups, which led to an irreversible reduction of FAV.…”
Section: Resultsmentioning
confidence: 99%
“…Pristine pyrazine itself belongs to the first group in which it is reversibly reduced to protonated 1,4‐dihydropyrazine by accepting two electrons and three protons. Its reversibility was decreased by the substitution of electron ‐withdrawing or ‐donating groups, and the reversibility can change based on electrode type and supporting electrolyte used [ 50 , 51 ]. The CVs show that the reduction of FAV is included in the third category because the pyrazine ring in the FAV molecule was substituted with three different groups, which led to an irreversible reduction of FAV.…”
Section: Resultsmentioning
confidence: 99%
“…At pH < 11, rapid decomposition is observed even at the CV time scale. Hjelm et al confirmed a degradation mechanism via protonation of the N atoms followed by tautomerization resulting in loss of aromaticity and redox activity . Substitution at the 2- and 3-positions (ortho to N) in quinoxaline can mitigate such a decomposition and improve chemical stability.…”
Section: Multielectron Organic Molecules In Aqueous Rfbsmentioning
confidence: 99%
“…After this theoretical study, the same group published an article in which they focused on single molecule pyrazines and quinoxalines in a voltametric study. Next to the different quinoxalines, they focused on six methylated as well as carboxylated pyrazine molecules [124] published in this issue. Unfortunately, they analyzed the first redox transition in slightly alkaline solutions (pH = 13) but not in the highly acidic region.…”
Section: Pyrazines (One Ring)mentioning
confidence: 99%
“…Increased overpotential on the negative side and gassing were observed during cycling of the cell. Another study was conducted by Hjelms' group on substituted pyrazines and quinoxalines, already cited above [124]. In this study, they substituted quinolines in the sixth and seventh position with methyl or carboxylic groups and looked at the influences in the voltammogram in slightly alkaline conditions (pH = 13) with sodium chloride as conducting salt.…”
Section: Quinoxalines (Two Rings)mentioning
confidence: 99%